Compósitos fúngicos: desenvolvimento de biomateriais a partir de resíduos agroindustriais - Bozzo, Breno Rampinelli (Universidade Federal de São Carlos, 2025)
The increase in the generation of agro-industrial residues and by-products, as well as their negative environmental impacts, has driven the search for sustainable alternatives across different sectors, promoting circular economy principles and sustainability-oriented practices. In this context, fungal composites emerge as highly relevant materials, as they are produced through the direct growth of fungi on lignocellulosic residues without requiring extensive pre-treatments, transforming these wastes into high value-added materials that can be reintegrated into the productive chain. This study aims to conduct a bibliographic review on the by-products, fungal species, and methodologies employed in the production of these materials, as well as their physicochemical properties and the potential applications that can be derived from them. The analyzed species — Pleurotus ostreatus, Ganoderma lucidum, and Trametes versicolor — belong to the group of white-rot fungi due to their high capacity to completely degrade lignocellulosic substrates, with the focus directed toward residues generated by Brazilian agricultural production.
Fungal composites: development of biomaterials from agroindustrial waste
Keywords: Compósitos fúngicos; Micélio; Resíduos agroindustriais; Sustentabilidade; Biomateriais; Fungal composites; Mycellium; Agroindustrial residues; Biomaterials; Sustentability; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; 12. Consumo e Produção Responsáveis